Avaliação de proteases e biossurfactantes produzidos por Bacillus subtilis TIM27 como aditivos em detergente - Araújo, Francisco Jonathan dos Santos (2020)
The growing demand of modern society for ecofriendly cleaning products has stimulated the search of natural additives and biodegradable products. Since petroleum-derived surfactants added to commercial enzymes are the key components of the major cleaning products, the replacement of synthetic these surfactants by biosurfactants supplemented with microbial enzymes is an alternative for the new generation cleaning products. However, the adverse laundry conditions such as extreme alkaline pH, has encourage the prospection of new and more stable molecules for this application. Therefore, this study aimed the evaluation of enzymes and biosurfactants produced by Bacillus subtillis TIM27 as commercial detergent additives. Biosurfactants (BIOS27) were produced using Surfactin Broth and partially purified by acid precipitation. Whereas enzymes were produced by cultivation in Nutrient Broth supplemented with glycerol 0.2% and subjected to precipitation with ammonium sulfate in the saturation ranges of F0-40% F40-70% and F70-90%, monitoring of esterase and proteolytic activity through the formation of hydrolysis halos in Nutritive Agar containing 0.1% tributyrin or 1% skim milk, respectively. The influence of pH values (6 -11) and NaCl concentration (0.5 - 4 M) were evaluated on F40-70% proteolytic activity and BIOS27 emulsifying activity. In addition, the ideal temperature (20 - 80 °C) of F40-70% proteolytic activity as well as the influence of 1% detergents (Triton X-100, Tween 80 and SDS), 7 mg/mL OMO®, 5 mM of metal ions (K +, Na +, Ca2 +, Mg2 +, Mn2 +, Cu2 + and Zn2 +) and 1 and 5 mM protease inhibitors (β-Mer, PMSF and EDTA). Experiments for enzyme identification after purification in ion exchange chromatography followed by hydrophobic chromatography were performed using mass spectrometry (ESI-Q-TOF). F40-70% and BIO27 were tested for washing performance using egg yolk emulsion impregnated in cotton fabrics. As results, it was observed that the F40-70% fraction showed proteolytic and esterase activities mainly due to the presence of a 39.4 kDa alkaline subtilisin identified by mass spectrometry. The crude fraction F40-70% showed higher proteolytic activity at pH 8.0, 50 ºC and showed stability in the presence of the OMO® commercial detergent. However, it showed 40% activity reduction in EDTA and total activity inhibition by SDS and Zn+ 2 ion. BIOS27 presented an excellent emulsion index of 66.6% and ability to reduce the surface tension of water to 25.3 mN/m, even in the presence of alkaline pH (pH 11.0) and high concentration of NaCl (2.0 M). Qualitatively, the combination of F40-70%, enriched with subtilisin, and biossurfactant BIOS27 showed equivalent performance to commercial OMO® detergent for cleaning egg yolk stain on cotton fabric. The incorporation of F40-70% in a heated OMO® solution also proved to have better activity to remove these stains than the endogenous enzymes of the commercial product, showing the great potential of these biomolecules in detergent formulations.